2016
DOI: 10.5535/arm.2016.40.5.915
|View full text |Cite|
|
Sign up to set email alerts
|

Physiological Responses During the Lower Body Positive Pressure Supported Treadmill Test

Abstract: ObjectiveTo quantify changes in cardiopulmonary function using a lower body positive pressure supported (LBPPS) treadmill during the exercise tolerance test (ETT) in healthy subjects before applying the LBPPS treadmill in patients with gait problems.MethodsWe evaluated 30 healthy subjects who were able to walk independently. The ETT was performed using the Modified Bruce Protocol (stages 1–5) at four levels (0%, 40%, 60%, and 80%) of LBPPS. The time interval at each level of the LBPPS treadmill test was 20 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…The compression exerted by the lower-body positive pressure treadmill during 40% off-loading is similar to standing in a swimmingpool unrelated to muscle use. We have demonstrated decreased heart rate during weight offloading during standing [44], recently shown by others during increasing levels of exertion during LBPP [72]. We speculate that there is synergy between standing and positive lower body pressure which would cause local hypoxia increasing muscle perfusion and oxygen uptake [73,37] as in pre-conditioning, thus potentiating the effects of the low intensity exercise improving mitochondrial function.…”
Section: Baro-physiologysupporting
confidence: 51%
“…The compression exerted by the lower-body positive pressure treadmill during 40% off-loading is similar to standing in a swimmingpool unrelated to muscle use. We have demonstrated decreased heart rate during weight offloading during standing [44], recently shown by others during increasing levels of exertion during LBPP [72]. We speculate that there is synergy between standing and positive lower body pressure which would cause local hypoxia increasing muscle perfusion and oxygen uptake [73,37] as in pre-conditioning, thus potentiating the effects of the low intensity exercise improving mitochondrial function.…”
Section: Baro-physiologysupporting
confidence: 51%
“…First, the reduced load condition in the study by Denning et al 33 was achieved by unloading with the hyperbaric treadmill. Being in a hyperbaric chamber increases the pressure acting upon the lower body, and systolic blood pressure increases when walking on a hyperbaric treadmill indicating reduced blood circulation in the lower extremities 34 . Reduced blood circulation presumably also reduces the systemic circulation of blood constituents 35 and hence may affect serum concentrations, possibly explaining the lacking load-induced changes in sCOMP with the reduced load condition reported by Denning et al 33 Second, it is possible that joint load at 40% lower BW is too low to act as a mechanical stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Denning et al 33 reported a greater load-induced increase in sCOMP when walking for 30 min with 140% body weight (BW) than with normal BW but observed no difference in load-induced increase in sCOMP between walking with 60% BW and normal BW. However, unloading was facilitated by a pressurized chamber on the lower body which reduces blood flow in the lower extremities reflected by increased systolic blood pressure 34 and hence likely limit the circulation of COMP in serum during the exercise 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, providing body weight support (BWS) allows for attenuation of the biomechanical risks of running so that movements can safely be repeated and improved, potentially allowing athletes to increase training volume or return to running sooner following injury or surgery. However, athletes using LBPPT may experience a cardiovascular fitness decline because of the task’s decreased aerobic demands without modifying the treadmill velocity at which they run [ 9 , 10 , 12 , 16 24 ].…”
Section: Introductionmentioning
confidence: 99%